Biodecolorization of methyl orange by mixed cultures of brown-rot fungus Daedalea dickinsii and bacterium Pseudomonas aeruginosa - Adi Setyo Purnomo; Mitha Ocdyani Mawaddah (Society for Indonesian Biodiversity, 2020)
Abstract. Purnomo AS, Mawaddah MO. 2020. Biodecolorization of methyl orange by mixed cultures of brown-rot fungus Daedalea dickinsii and bacterium Pseudomonas aeruginosa. Biodiversitas 21: 2297-2302. This study investigated on the decolorization of methyl orange (MO) by mixed cultures of brown-rot fungus (BRF) Daedalea dickinsii and bacterium Pseudomonas aeruginosa. P. aeruginosa was added into D. dickinsii culture at 2, 4, 6, 8, 10 mL (1 mL = 5.05 × 1012 CFU). All of mixed cultures had ability to decolorize MO (final concentration 100 mg/L) in potato dextrose broth (PDB) medium for 7 days incubation. The addition of 4 mL of P. aeruginosa showed the highest MO biodecolorization approximately 97,99%, while by D. dickinsii only was 67,54%. C15H19N3O5S; C16H21N3O5S; C17H23N3O6S; and C15H19N3O6S were identified as MO metabolites. This study indicated that mixed cultures of D. dickinsii and P. aeruginosa have great potential for high efficiency, fast and cheap dye wastewater treatment.